The Influence of Industrial Value Added Level and Carbon Dioxide (CO2) Emission Level on China's Economic Growth 1994 – 2023 - Heri Susilo, Tomy Irawan; Fuddin, Muhammad Khoirul (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2025)
The economic conditions of a country determine the level of welfare of its people, which means that every country wants high and sustainable economic growth. This research aims to analyze how industrial value added and carbon dioxide emissions affect economic growth. The object of this research is China. This quantitative research type uses time series data. The data analysis used in this study is a multiple linear regression model. This research uses time series data of the year 1993-2023, together with the variables of industrial value added, carbon dioxide emissions and gross domestic product. The results show that industrial value added has a positive and significant effect on China's economic growth. In contrast, carbon dioxide emissions have a positive but not substantial impact on China's economic growth.